'It's Training Man'! Membership Categorization and the Institutional Moral Order of Basketball Training. Issue 2 (2nd April 2016) - Evans, Bryn; Fitzgerald, Richard
Abstract : In this paper we examine how physical and verbal actions are constituted as morally accountable within an institutional context. Through the detailed examination of a video recording of the aftermath of an on-court altercation between players in a basketball training session, we explore how the members work to establish a locally organized institutional context for an action within which in situ moral reasoning practices are then brought to bear to make sense of the players' actions and render them as morally accountable or not. In examining the moral organization of institutional accountability in an instance of basketball training activity, the paper develops a further level of detail to understand the reflexive organization of membership categories and the institutional moral order.